A Case Study to Risk Assessment for Protecting Airports against Lightening - Tarımer, İ. and Kuca, B. and Kisielewicz, T. (Elektronika ir Elektrotechnika, 2012)
An airport has numerous structures, systems, buildings, runways and components that are susceptible to lightning strikes. The effects of strikes can include actuation of safety systems, and loss of fire protection. Flashes to the structure, runway roads, the lines connected to the structure can cause injury to people, physical damage of takeoff and landing runways and aircraft’s ramps, failure of internal electrical and electronic systems. Hence the need for protection of critical structures and selection of protection measures should be determined in terms of risk. If the lightning threats, all risk events estimated, the consequences of the risk events determined are above a tolerable level of risk, protection measures are applied to reduce the risk (R) to below the tolerable level (RT). In this study, the criterions for reducing physical damages and life hazard due to direct lightning flashes have been determined. Ill. 1, bibl. 10 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1052